Antara MK dan Demokrasi: Menilik Kembali Putusan MK No. 90 yang Merusak Demokrasi Indonesia. - Arga, Feliks (Dekonstruksi, 2025)
The Indonesian Constitutional Court in 2023 made a verdict that changed the electoral process in Indonesia. The decision, known as Constitutional Court Decree No. 90 in 2023, paved the way for Gibran Rakabuming Raka, the son of former president Joko Widodo, to run as the vice presidential candidate alongside Prabowo Subianto as the presidential candidate. This hurt the Indonesian democratic election that was taking place at the time. As the son of the incumbent president, Gibran's advancement as a vice presidential candidate by changing the existing law perpetuated the practice of nepotism—the same principle that was fought against by reform in 1998. Through this paper, the author aims to show how far the decisions are actually guided by the moral ethics of law in Indonesia and how the decisions undermine the dignity and value of democracy in Indonesia by perpetuating nepotism in the nomination of presidential and vice presidential candidates in the 2024 general elections.